Service Quality and Emotional Experience as Key Drivers of E-Wom in the Hospitality Sector - Muhammad Zain Maajid; Mahmud Mahmud; Tubagus Achmad Darodjat (Jurnal Telekomunikasi dan Informatika, 2025)
This study aims to examine the effect of service quality and positive emotional experience on customer satisfaction and positive eWOM at Patra Semarang Hotel & Convention. Service quality and positive emotional experience are considered important factors that can increase customer satisfaction and influence the behavior of sharing positive experiences through digital platforms. The research method used is a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). Data were collected through an online questionnaire distributed to 181 respondents who had stayed at the hotel. The results showed that service quality has a significant positive effect on customer satisfaction and positive eWOM. Positive emotional experience also has a significant effect on customer satisfaction, but does not have a direct effect on positive eWOM. In addition, customer satisfaction is proven to function as a mediator connecting service quality and positive eWOM. These findings underline the importance of improving service quality and attention to customer emotional experiences to encourage them to share positive experiences online. The implications of this study suggest that hotel managers need to prioritize service quality and create pleasant emotional experiences to increase customer satisfaction and utilize positive eWOM as an effective promotional tool. This research contributes to theory development in hospitality, by providing a deeper understanding of the role of service quality and emotional experiences in creating customer satisfaction and positive experience sharing behavior.